MAVLONO JALALIDDIN RUMIY AND HOJA AHROR (Conference Zone, 2022)
The article compares similar situations in the works of Jalaliddin Rumi and Khoja Ahror Wali. Mawlana Jalaliddin Rumi's works "Masnavii Ma'navi" and "Fihi ma fihi" (Inside is inside) are considered to be the encyclopedia of spirituality. In his work, Hoja Ahror discusses man, humanity and human truth, dialogue, respect for the teacher-teacher and its importance in the upbringing of a harmoniously developed person.